Interactions Between Enteroviruses and the Inflammasome: New Insights Into Viral Pathogenesis - Xiao, Xia; Qi, Jianli; Lei, Xiaobo; Wang, Jianwei (Frontiers in Microbiology, 2019)
Enteroviruses (EVs) have emerged as substantial threats to public health. EVs infection range from mild to severe disease, including mild respiratory illness, diarrhea, poliomyelitis, hand, foot, and mouth disease, aseptic meningitis, and encephalitis. In the Asia-Pacific region, for example, one of the best studied enterovirus 71 (EV71) has been associated with pandemics of hand, foot, and mouth disease (HFMD) in children, particularly those under the age of five. Serious HFMD cases are associated with neurological complications, such as aseptic meningitis, acute flaccid paralysis, brainstem encephalitis, and have been associated with as many as thousands of deaths in children and infants from 2008 to 2017, in China. More than 90% of laboratory confirmed deaths due to HMFD are associated with EV71. However, little is known about the pathogenesis of EVs. Studies have reported that EVs-infected patients with severe complications show elevated serum concentrations of IL-1β. The secretion of IL-1β is mediated by NLRP3 inflammasome during EV71 and CVAB3 infection. Enteroviruses 2B and 3D proteins play an important role in activation of NLRP3 inflammasome, while 3C and 2A play important roles in antagonizing the activation of NLRP3 and the secretion of IL-1β. In this review, we summarize current knowledge regarding the molecular mechanisms that underlie the activation and regulation of the NLRP3 inflammasome, particularly how viral proteins regulate NLRP3 inflammasome activation. These insights into the relationship between the NLRP3 inflammasome and the pathogenesis of EVs infection may ultimately inform the development of novel antiviral drugs.